2019
DOI: 10.1152/ajpcell.00483.2018
|View full text |Cite
|
Sign up to set email alerts
|

STF-62247 accumulates in lysosomes and blocks late stages of autophagy to selectively target von Hippel-Lindau-inactivated cells

Abstract: Autophagy is a highly conserved, homeostatic process by which cytosolic components reach lysosomes for degradation. The roles played by different autophagic processes in cancer are complex and remain cancer type and stage dependent. Renal cell carcinoma (RCC) is the most common subtype of kidney cancer and is characterized by the inactivation of the von Hippel-Lindau (VHL) tumor suppressor. Our previous study identified a small compound, STF-62247, as an autophagy-modulating molecule causing selective cytotoxi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
2
16
2
Order By: Relevance
“…Moreover, we speculate that short-time as well as lower-dose treatment with pimozide triggers autophagy as well as selective degradation of mitochondria, but does not exceed the threshold required for lethal autophagy, as we did not detect a marked induction of cell death in these settings. Interestingly, in contrast to our findings that classify STF-62247 as an inducer of autophagic flux and ACD, STF-62247 has recently been reported to block late stages of autophagy by inducing lysosomal disruption in von Hippel-Lindau (VHL)-deficient renal cell carcinoma cells 80 . This study however emphasized that VHL-competent cells are capable to overcome this block of late stages of autophagy and to maintain high lysosome numbers, which is consistent with our data showing that STF-62247 enhances the autophagic flux of VHL-competent MEFs as well as GBM cell lines 30,80 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Moreover, we speculate that short-time as well as lower-dose treatment with pimozide triggers autophagy as well as selective degradation of mitochondria, but does not exceed the threshold required for lethal autophagy, as we did not detect a marked induction of cell death in these settings. Interestingly, in contrast to our findings that classify STF-62247 as an inducer of autophagic flux and ACD, STF-62247 has recently been reported to block late stages of autophagy by inducing lysosomal disruption in von Hippel-Lindau (VHL)-deficient renal cell carcinoma cells 80 . This study however emphasized that VHL-competent cells are capable to overcome this block of late stages of autophagy and to maintain high lysosome numbers, which is consistent with our data showing that STF-62247 enhances the autophagic flux of VHL-competent MEFs as well as GBM cell lines 30,80 .…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, in contrast to our findings that classify STF-62247 as an inducer of autophagic flux and ACD, STF-62247 has recently been reported to block late stages of autophagy by inducing lysosomal disruption in von Hippel-Lindau (VHL)-deficient renal cell carcinoma cells 80 . This study however emphasized that VHL-competent cells are capable to overcome this block of late stages of autophagy and to maintain high lysosome numbers, which is consistent with our data showing that STF-62247 enhances the autophagic flux of VHL-competent MEFs as well as GBM cell lines 30,80 . From a mechanistic perspective, this could be due to STF-62247-induced inhibition the master regulator of autophagy, mTORC1, which we demonstrated in our previous study in GBM cells 30,81 .…”
Section: Discussioncontrasting
confidence: 99%
“…7), where the cells appeared flattened under an inverted microscope as previously reported 8 . However, we also observed a curious cellular morphology of enlarged cytoplasmic vesicles that prompted us to test whether the enlarged structures were lysosomes 15 . Enlarged lysosomes are typically discernible with the DIC (differential interference contrast) brightfield microscopy.…”
Section: Rev1 Inhibition Triggers Autophagy a Radioresistance Biomarkermentioning
confidence: 98%
“…For instance, Turcotte et al screened VHL-deficient and VHL-reconstituted RCC4 cells with a 64,000 drug compound library, and identified that STF-62247 selectively killed the VHL-deficient cells [87]. Cell death was HIF independent and thought to be mediated by STF-62247 accumulation in lysosomes, and inhibition of late stage autophagy [88]. Thompson et al also used RCC4 cells, and screened with a library of pharmacologically active compounds [89].…”
Section: Accepted Articlementioning
confidence: 99%